(1587) energy-economic interaction-models :a review-models : a review نماذج التفاعل بين الطاقة والاقتصاد: مراجعة - نماذج: مراجعة - zaghloul, fathia (The Institute Of National Planning., 2018)
During the last years, interest in energy problems has considerably increased all over the world. The use of energy is becoming one of the primary determinants of GDP growth, and it can be considered, even, as a measure to the rate of development of the economy.